Makrofauna Permukaan Tanah Di Bawah Satuan Pohon Campuran Alpukat, Kakao, dan Kopi Di Desa Senaru Lombok Utara - Adinda Utami, Annisa; Susilowati, Lolita Endang; Jaya, Dori Kusuma; Azizah, Isnaniar Rahmatul (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The presence of soil macrofauna can serve as an indicator of land quality changes, as high macrofaunal diversity generally reflects a healthier ecosystem. This study aims to assess soil macrofauna diversity in agroforestry land in Senaru Village, North Lombok, to provide an overview of soil ecosystem conditions in the area. The research was conducted in the Special Purpose Forest Area of Senaru Village on mixed tree stands of avocado, cacao, and coffee, from October to September 2023. The study employed a descriptive-quantitative method using the pitfall trap technique to collect macrofauna. Data were analyzed using Margalef’s species richness index (R), Shannon-Wiener diversity index (H’), and Pielou’s evenness index (E’).  The results indicate that the soil is slightly acidic (pH 6.4), with a moderate organic carbon content (2.45%) and adequate moisture levels (57%). High soil temperature (35°C) contributes to increased organic matter decomposition, while a litter layer thickness of 6.5 cm helps maintain soil moisture. Macrofauna diversity was classified as moderate, dominated by the phylum Arthropoda, particularly the family Formicidae (134 individuals). The families Rhoppalidae (Hemiptera) and Isotomidae (Collembola) were also abundant. Species richness indices showed that coffee and cacao stands had moderate species richness, whereas avocado had lower values. Macrofauna evenness was uneven, with the highest distribution in coffee stands (47%) and the lowest in avocado (34%). These findings suggest that the agroforestry land in Senaru Village still supports soil macrofaunal diversity, with tree species variations influencing species distribution and richness.